Factors Affecting Pregnancy Rate in Infertile Women Underwent in Vitro Fertilization / Intracytoplasmic Sperm Injection Cycle - Wafaa Mohammed Al-Jubouri, Manal Taha Al-Obaidi, Huda Ali Hussaini (Pakistan Journal of Medical & Health Sciences, 2023)
Intracytoplasmic sperm injection is more being used for non-male factor indications, although it was developed for overcoming infertility of males because pregnancy rate of in vitro fertilization is still < 40%. This work aims at evaluating the vitro sperm injecting cycle fertilization/ Intracytoplasmic efficiency in infertile women and the factors that predicting clinical pregnancy rate. Al-Nahrain University at the High Institute for Infertility Diagnosis and Assisted Reproductive Technologies, we conducted a randomized clinical trial from 1st Sep. 2018 to 1st Sep. 2020. 40 women complaining from infertility underwent IVF / ICSI protocols were sampled for this work. Positive serum βhCG test were used to evaluate pregnancy r, two weeks following transferring embryo. In this study, 12 infertile women got pregnant with pregnancy rate of 30%. Duration of stimulation, number of mature eggs, fertilized eggs, and grade I transferred embryo, and changes in percentages in endometrial zone at day of pickup in comparison with that at day of hCG were significantly higher (P < 0.05) in pregnant women than those who were not pregnant. Failure rate of pregnancy is still high and the most important factors that associated with failure of IVF/ICSI outcome were short duration of gonadotropin stimulation, few number of mature eggs and embryos, and suboptimal endometrial receptivity. Keywords: IVF, ICSI, infertility, pregnancy rate, predictors, Iraq.